Real-world clinical outcomes and rationale for initiating abatacept as a first-line biologic for patients with anticitrullinated protein antibody- and rheumatoid factor-positive rheumatoid arthritis - Alexandrina Balanean; Cherrishe Brown-Bickerstaff; Andrew Klink; Vardhaman Patel; Hanke Zheng; Laetitia N'Dri; Keith Wittstock; Bruce Feinberg; Mark Chaballa; Vadim Khaychuk; Jill Kaufman; Prathamesh Pathak; et al. (Becaris Publishing Limited, 2024)
Aim: In rheumatoid arthritis (RA), seropositivity for both anticitrullinated protein antibody (ACPA) and rheumatoid factor (RF) is associated with disease severity and therapeutic response. Biologic (b) diseasemodifying antirheumatic drugs (DMARDs) such as abatacept are recommended after inadequate response or contraindication to conventional synthetic DMARDs. This retrospective cohort study aimed to describe changes in Clinical Disease Activity Index (CDAI) measures over 12 months among patients with ACPA+ and RF+ RA with an inadequate response to methotrexate treated with abatacept as a first-line bDMARD. Patients & methods: Patient data were abstracted from medical records by treating rheumatologists. Analyses included McNemar tests for paired proportions or paired t-tests to assess longitudinal changes in CDAI scores, and Kaplan-Meier methods for time-to-event outcomes. Serious AEs and rationale for initiating treatment were recorded. Results: Overall, 296 patients were included. Mean CDAI scores improved (decreased) by 34.0, 61.0 and 74.0% (all p < 0.001) from baseline to 3-6 months, 6-12 months and ≥12 months after abatacept initiation, respectively. Of 279 patients not in CDAI low disease activity (LDA) or remission at baseline, 24.7% of patients achieved it within 6 months, 56.3% within 12 months and 71.0% at any point during follow-up after abatacept initiation. Median time to CDAI LDA/remission was 10.2 months. Serious AEs were reported in 2.4% of patients. Common reasons reported by rheumatologists for initiating abatacept were effectiveness/efficacy (52.7%), safety (31.4%) and patient preference (25.3%). Conclusion: In this analysis of patients with ACPA+ and RF+ RA treated with abatacept as a firstline bDMARD in a clinical practice setting, clinical outcomes and remission rates were improved at all time points, providing real-world evidence to further support the use of abatacept in this patient population.